2018
DOI: 10.1038/s41416-018-0093-y
|View full text |Cite
|
Sign up to set email alerts
|

Tumour buds determine prognosis in resected pancreatic ductal adenocarcinoma

Abstract: Background The prognostic effect of tumour budding was retrospectively analysed in a cohort of 173 patients with resected pancreatic ductal adenocarcinomas (PDACs) of the prospective clinical multicentre CONKO-001 trial. Methods Haematoxylin and eosin (H&E)-stained whole tissue slides were evaluated. In two independent approaches, the mean number of tumour buds was analysed according to the consensus criteria in colorectal cancer, in one 0.785 mm 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 34 publications
2
39
0
Order By: Relevance
“…Methods 1 and 2 were based on work by Karamitopoulou E et al 21 and Ueno H et al 32 and the recommendations of ITBCC 12 . Method 3 was inspired by Lohneis P et al 24 applying ten 0.238 mm 2 fields of view. Finally, Method 4-7 are novel approaches quantifying tumour buds across the whole slide or large regions of interest; methods only made feasible by the application of automated image analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Methods 1 and 2 were based on work by Karamitopoulou E et al 21 and Ueno H et al 32 and the recommendations of ITBCC 12 . Method 3 was inspired by Lohneis P et al 24 applying ten 0.238 mm 2 fields of view. Finally, Method 4-7 are novel approaches quantifying tumour buds across the whole slide or large regions of interest; methods only made feasible by the application of automated image analysis.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that TB reflects an early step in progression towards metastasis due to their cell's reported phenotypic epithelial to mesenchymal transition (EMT) [18][19][20] . Despite reports of observer variability, studies in other cancer types have continuously demonstrated the significant association of TB with adverse clinicopathological features and the independent significance of TB as a prognostic factor [21][22][23][24][25] . Information about the role of TB in bladder cancer is scarce 26 and it has not yet been reported to be associated with disease specific survival (DSS) in MIBC.…”
mentioning
confidence: 99%
“…2,8,9,11,12,20,27,34,40,45,48,54 This definition is in accordance with the recent recommendation by the International Tumor Budding Consensus Conference (ITBCC 2016) in colorectal cancer, 55 and also agrees with studies on other cancers. 56,57 Of note, a recent study has reported an excellent reproducibility and reliability of ITBCC 2016 scoring method in oral tongue cancer. 37 Majority of studies that assessing tumor budding in HNSCC have used one high-power field (HPF) in which the invasive front scanned and area with highest number of tumor budding is counted and used to score the case.…”
Section: Evaluation Of Tumor Buddingmentioning
confidence: 99%
“…2,12,37,54,59 High reproducibility has also been shown in many studies evaluating tumor budding in other cancers. 57,[62][63][64] This indicates eligibility of tumor budding to be routinely implemented in clinical reports. Assessment of tumor budding using digital image analysis of pan-cytokeratin stained slides has recently shown a promising correlation with patient survival in oral cancer 25,65 and in colorectal cancer as well.…”
Section: Evaluation Of Tumor Buddingmentioning
confidence: 99%
“…In particular, an increasing number of studies has shown the critical role of the immune contexture on patient survivability, suggesting that it could be a valuable determinant of patient prognosis [21,19]. Motivated by multiple papers [22,23,24,25], we investigate the prognostic role of tumour infiltrating lymphocytes (TILs), tumour-associated macrophages (TAMs), tumour buds (TBs), and programmed cell death-ligand 1 (PD-L1) in MIBC patients.…”
Section: Introductionmentioning
confidence: 99%